2006
DOI: 10.1002/lt.20804
|View full text |Cite
|
Sign up to set email alerts
|

Molecular adsorbent recirculating system in patients with early allograft dysfunction after liver transplantation: A pilot study

Abstract: Early allograft dysfunction (EAD) after orthotopic liver transplantation (OLT) causes marked morbidity and mortality. We conducted a prospective pilot study to assess the safety and efficacy of molecular adsorbent recirculating system (MARS) in treatment of EAD after OLT. Twelve consecutive adult liver allograft recipients with a median age of 48 years, 9 of whom were male, were prospectively included and supported with MARS. EAD was defined as the presence of at least 2 of the following: serum bilirubin Ͼ10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 26 publications
(35 reference statements)
0
15
0
Order By: Relevance
“…Multiple studies have demonstrated the efficacy of albumin dialysis in decreasing total bile acid pool and bilirubin concentration, providing relief of the clinical manifestations of cholestasis [43,44]. MARS treatment could be a useful tool in facilitating hepatic recovery in patients with severe drug-induced liver injury with features of cholestasis, posttransplant cholestasis due to graft dysfunction, and in liver failure patients awaiting transplantation [45,46,47 ]. Albumin dialysis is also effective in improving intractable pruritis from severe cholestasis in some patients with cholestatic conditions [48,49 ].…”
Section: Role Of Nonbiological Devices In Acute-on-chronic Liver Failurementioning
confidence: 99%
“…Multiple studies have demonstrated the efficacy of albumin dialysis in decreasing total bile acid pool and bilirubin concentration, providing relief of the clinical manifestations of cholestasis [43,44]. MARS treatment could be a useful tool in facilitating hepatic recovery in patients with severe drug-induced liver injury with features of cholestasis, posttransplant cholestasis due to graft dysfunction, and in liver failure patients awaiting transplantation [45,46,47 ]. Albumin dialysis is also effective in improving intractable pruritis from severe cholestasis in some patients with cholestatic conditions [48,49 ].…”
Section: Role Of Nonbiological Devices In Acute-on-chronic Liver Failurementioning
confidence: 99%
“…Studies have suggested that MARS therapy improved the hemodynamic situation in patients with acute and acute-on-chronic liver failure [95]. Several groups observed an increase in arterial pressure, systemic vascular resistance index, a decrease in portal pressure and improvement of renal blood fl ow [95][96][97][98][99][100]. MARS may therefore be a therapeutic option of potential interest in patients with HH.…”
Section: Marsmentioning
confidence: 99%
“…Thus, it is mostly confined to the intravascular space, with minimal leakage, even from abnormal or fenestrated vessels 3. Under physiological conditions, ICG is exclusively eliminated from the blood through the liver and excreted chemically unchanged into the bile 3–6…”
mentioning
confidence: 99%